Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi as indicators of land-use severity in managed woodlands dominated by Quercus suber — a case study from southern Portugal - Azul, Anabela Marisa; Castro, Paula; Sousa, José Paulo; Freitas, Helena (Canadian Journal of Forest Research, 2009)
We assessed the impacts of current management practices used to control shrub strata in Portuguese oak woodlands dominated by Quercus suber L. (montado) on fruiting diversity and abundance of ectomycorrhizal-forming fungi (ECMF) and saprobic fungi. Fruit bodies were collected over four fruiting seasons in 16 plots (20 m × 20 m) selected in a montado landscape with extensive silvopastoral exploitation. A total of 9484 fruit bodies were found in 171 taxa (74 ECMF, 96 saprobic, and 1 parasitic). Our results show that shrub density control by permanent grazing or by cutting practices followed by soil tillage leads to lower fruiting production and greater changes in taxa composition, particularly for ECMF fruit bodies, than cutting practices without soil tillage. Principal response curve analysis showed that ECMF reacted more sensitively to these practices, in particular Laccaria laccata, Hebeloma cistophilum, Russula cyanoxantha, Cortinarius trivialis, and Lactarius volemus. We also observed that shrub cutting without soil tillage allowed ECMF fruiting to recover to predisturbance levels after 3 years. Our data imply that fruit bodies were useful indicators for assessing the severity of the effects of different land-use practices applied in montado areas on soil fungal populations.
doi: 10.1139/X09-148doi: 10.1139/X09-148The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: diversity; fruiting patterns; fungi; montado (voyant); shrub management; Tillage